The poetics of fragmentation: structure and writing in Alejandro Zambra’s Formas de Volver a Casa - Amaro, Jaime (Árboles y Rizomas, 2019)
The present article analizes Alejandro Zambra’s novel Ways of Going Home considering its structure and the way of writing that it draws on. In order to do so, Carlos Hernandez’ nominations about the poetics of fragments are considered.  In this context, it explains the fragmentariness and the metafiction of the writing as strategies that reflect the Chilean post-dictatorial disintegration and the way that this resource is used to find a suitable language to properly portray grief.
Keywords: Alejando Zambra; Ways of Going Home; fragments; metafiction; writing